Education Policies in Turkey during the Rule of the Justice and Development Party (AK Party) - Esergül BALCI (İnsan&İnsan Bilim Kültür Sanat ve Düşünce Dergisi, 2021)
In this study, the National Education Policies implemented by the Justice and Development Party (AK Party) were examined. After scanning the literature, AK Party’s party programs, its government programs, the National Education Councils (MEŞ) and the State Planning Organization Five-Year Development Plans (DPTBYKP) were discussed. During the analysis, it has been observed that the understanding of orientation towards religious education has emerged with the privatization adopted by the AK Party in the economic field, and the number of private schools at all levels has been increased with state support. It has been also seen that as a result of this privatization, wealthy families have preferred to send their children to private schools, thinking that they are more qualified. As a social result of this, “equality of opportunity in education” has deteriorated, poor family children have not had the chance to benefit from quality education, and some students are out of the system after eight years of training.